SPECTROPHOTOMETRIC ANALYSIS OF CHLORAMPENICOL IN TIGER PRAWNS (PENAEUS MONODON) BASED ON THE DIAZOTATION REACTION - Indra Kurniawan; Moh. Syaiful Arif; Bohari Yusuf (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Spectrophotometric analysis of chloramphenicol in tiger prawns (Penaeus Monodon) based on the diazotation reaction has been carried out. Sulfanilamide is used as a source of diazo salt to be coupled with chloramphenicol. In this study, several optimizations were carried out such as optimization of temperature, volume of HCl, volume of NaNO2, volume of sulfanilamide and contact time. Diazonium salt coupled with sulfanilamide produces a clear yellow compound with a maximum wavelength of 400.941 nm. The results of the analysis chloramphenicol on tiger shrimp, obtained the coefficient of variation were 4.026 %; 1.951 %; and 4.277 %.. Accuracy ranges from 99.7143% to 100.8730%. The Limit of Detection value is 6.24 mg/mL and the Limit of Quantization value was 20.803 mg/mL. The sensitivity value is 0.0021 mL /mg.